Factors that lead Malaysians to file for personal bankruptcy - Mohamed, Suhana; Nayan, Mohamad Arif; Ismail, Azianti; Omar, Nooririnah; Romli, Nurulashikin (Human Resource Management Academic Research Society, 2022)
A formal legal statement that one cannot fully repay all of one's debts is required to declare bankruptcy. Since 2000, the number of personal bankruptcies that occur annually in Malaysia has been greater than 10,000. The COVID-19 outbreak that began in early 2020 had a significant negative impact on the economy and the healthcare system as if things were not already terrible enough. As a result, the primary objective of this study was to investigate the statistics covering the period from 1990 to 2020 to determine the factors that lead to personal bankruptcies in Malaysia. In addition, it examined whether or not there was a connection between individual bankruptcies in Malaysia and the country's lending rate, the percentage of loans that were considered to be non-performing, and the unemployment rate. A multivariate regression model was utilized to determine the significance of the relationship between the dependent and independent variables. It was discovered that individual bankruptcies had a significant and inversely proportional relationship with credit and unemployment rates. On the other hand, there was a significant connection between personal bankruptcies and the presence of non-performing loans. Future researchers are strongly encouraged to gather data daily, quarterly, or monthly, incorporate more independent factors in the drivers of personal bankruptcy, and expand their investigations to other countries to obtain more accurate and credible conclusions.